Supporting Students' Speaking Skill in ELT Classroom: An Exploratory Action Research - Oli, Indra Kumari (Journal of Janta Multiple Campus, 2024)
The purpose of this Exploratory Action Research (EAR) was to explore the reasons behind the reluctance of students to speak in ELT class and to come up with possible solutions. It is based on an exploratory research design following a questionnaire, focused group discussions, and reflective notes as the tools for data collection. To investigate and overcome the issue, a set of questionnaires (open and close-ended were made in MS Word and Google Forms) and asked the students studying in grade 8 aged 13- 15 years old. I additionally used my reflective journals and had informal discussions with the focused group of 7 students to gather the data. After analyzing the data statistically and thematically, I found that my students liked to communicate in English but avoided it because of the fear of making mistakes and being laughed at by their peers. After devising the plans like asking the students to make self-suggestive and reflective notes, clapping instead of laughing while someone speaks in English, creating learner autonomy in the classroom, focusing on group and pair activities and providing complete and clear instructions in English helped to enhance the speaking skill of my students.